RP-HPLC-DAD Method Development and Validation for 1,3,4-Oxadiazole Derivative to Evaluate Its Forced Degradation Behavior and Stability - Deshpande, Shridhar Narayan; BC, Revana Siddappa; Khot, Kartik Bhairu; Rajesh, Gupta Dheeraj; Lobo, Cynthia Lizzie (Journal of Health and Allied Sciences NU, 2024)
In the current study, a straightforward high-performance liquid chromatographic (HPLC) approach was developed and validated to identify a novel drug compound called 5-(4-bromophenyl)-N-(2-chloro-4-nitrophenyl)-1,3,4-oxadiazol-2-amine (A3). By putting the compound's solution under hydrolytic, oxidative, and photolytic stress, the method's capacity to detect stability was put to the test. A gradient mobile phase of acetonitrile, orthophosphoric acid, and methanol (90:051:05 v/v), at a flow rate of 1.00 mL/min, was used for the chromatographic separation on a C18 column (Promosil, 5μ, 4.60 250 mm), which was maintained at 40°C and a photodiode array detector was used for detection. At concentrations between 10 and 100.00 μg/mL, Beer's rule was observed. The recovery (99.25–100%, standard deviation [SD] 5%), intraday accuracy and precision (98.62–99.91%, relative standard deviation [RSD] 5%), interday accuracy and precision (96.25–99.91%, RSD 5%), and intermediate accuracy and precision (98.10–99.91%, RSD 5%) all indicated that the developed method was reliable, repeatable, reproducible, and robust. In cases of thermal and moisture deterioration, respectively, the compound's peak resolution and selectivity factors from the nearest resolving peak revealed specificity and selectivity. The selected synthesized compound barely broke down under oxidative and alkaline hydrolytic stress. However, the compound was resistant to photolysis in neutral and acidic environments. The results of this study demonstrate the sensitivity, specificity, and selectivity of the established approach for quality control, stability testing, and preformulation investigations.
Keywords: 1,3,4-oxadiazole derivative; column chromatography; RP-HPLC; forced degradation